Manufacturing extremism: Political consequences of profit-seeking media - Siddhartha Bandyopadhyay; Kalyan Chatterjee; Jaideep Roy (University of Birmingham, Birmingham Business School, 2015)
We analyze the consequences of a monopolistic, non-partisan, profit-maximizing media on policy divergence. The media undertakes costly coverage that may reveal the quality of an office-seeking political challenger only if quality-conscious voters pay an access fee. Voters are ideologically homogenous and the incumbent politican is a populist with known quality. We show that while media absence implies a populist challenger, media presence yields platform extremism: it creates demand for information about quality and provides incentives to the media to invest in coverage that are exploited by high-quality challengers to signal strength.
Keywords: C72; D72; D82; 330